Counterpart. The complete first season [videorecording (DVD)] - Simmons, J. K.; Choi, Kenneth; Dobrev, Rudy (Lions Gate Entertainment, 2018)
Howard Silk is a lowly cog in the bureaucratic machinery of a Berlin-based United Nations spy agency. When Howard discovers that his organization safeguards the secret of a crossing into a parallel dimension, he is thrust into a shadow world of intrigue, danger, and double cross, where the only man he can trust is his near-identical counterpart from this parallel world.